From ‘motherland’ to ‘daddy state’: A genealogical analysis of the gender undertone in China's nationalist discourses - Wang, Clyde Yicheng; Chen, Zifeng (Nations and nationalism, 2023)
This article examines the gender undertone of China's nationalist discourses, especially in familial metaphors of nationalism, and how such an undertone shapes people's understandings of state authority and state‐citizen relations. Conventional nationalist discourse of the ‘motherland’ evokes the image of an insulted and raped mother as the symbol of national humiliation and calls for actions from patriots (masculinised in the discourse). In recent years, however, we have seen the emergence of a new discourse that depicts the nation‐state as a rich, powerful and masculine ‘daddy’. Using discourse analysis and Foucauldian genealogical methods, this article argues that the discursive development has to be analysed against China's historical backgrounds, especially considering new standards of masculinity and femininity in the era of economic reform. Capital is equated to masculinity and righteousness, whereas femininity is shaped by the middle‐class values of consumerism and political disengagement. The ‘daddy state’ discourse conjures strong paternalistic power from China's economic capacity that can be projected onto challengers of state authority, while also constructing the nationalist public as feminised consumers whose consumerist enjoyment relies on patriarchal state protection.